The gift of the pirate queen - Giff, Patricia Reilly; Rutherford, Jenny (New York : Dell, 1983)
Sixth-grader Grace, her mother dead and her only sister ill with diabetes, learns to be brave like the pirate queen Grace O'Malley, whom her Irish cousin says she resembles.
Children's Catalog (Wilson)
Elementary School Library Collection (Bro-Dart)
Booklist v. 79
4.1
3-6
Keywords: Irish Americans -- Fiction; Death -- Fiction; Diabetes -- Fiction; Irish Americans -- Fiction; Death -- Fiction; Diabetes -- Fiction